Poin Dialog yang Korelasional dan Bertanggungjawab Global dalam Sekolah Lintas Iman - Rosario, Agustinus (Seminari Tinggi St. Fransiskus Xaverius Ambon, 2022)
This article aims to analyze the role of the Sekolah Lintas Iman (SLI, Cross-Faith School) as an interreligious dialogue program in the city of Yogyakarta in implementing a correlational and globally responsible dialogue. The main question to be answered is whether the activities carried out by SLI have reflected a correlational and globally responsible dialogue according to the Paul F. Knitter’s concept. The author uses the theory of Paul F. Knitter's dialogue model contained in the book One Earth Many Religions as a theoretical basis to discover the points of interreligious dialogue contained in it. The research was conducted by distributing questionnaires to former participant, conducting interviews with facilitators, and library research. In this research, the author tries to find the points of interreligious dialogue that are correlational and globally responsible in SLI’s activities, as well as looking for the contribution of SLI in Knitter's thinking.